2016
DOI: 10.3109/1547691x.2016.1140854
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the irritancy and hypersensitivity potential following topical application of didecyldimethylammonium chloride

Abstract: Didecyldimethylammonium chloride (DDAC) is a dialkyl-quaternary ammonium compound that is used in numerous products for its bactericidal, virucidal and fungicidal properties. There have been clinical reports of immediate and delayed hypersensitivity reactions in exposed individuals; however, the sensitization potential of DDAC has not been thoroughly investigated. The purpose of these studies was to evaluate the irritancy and sensitization potential of DDAC following dermal exposure in a murine model. DDAC ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 29 publications
3
32
1
Order By: Relevance
“…9 D). Meanwhile, contrary to our expectation ( Anderson et al, 2016 ), the level of IL-4 and IFN-γ showed the decreasing trend in the lung of both sexes of mice treated with DDAC compared to control, and the levels of most of cytokines (or chemokines) were not significantly different between groups ( Supplementary Fig. 5 ).…”
Section: Resultscontrasting
confidence: 96%
“…9 D). Meanwhile, contrary to our expectation ( Anderson et al, 2016 ), the level of IL-4 and IFN-γ showed the decreasing trend in the lung of both sexes of mice treated with DDAC compared to control, and the levels of most of cytokines (or chemokines) were not significantly different between groups ( Supplementary Fig. 5 ).…”
Section: Resultscontrasting
confidence: 96%
“…both ACD and asthma) (De Vooght et al ., 2010; Matheson et al ., 2005). The quaternary ammonium compound (QAC), didecyldimethylammonium chloride (DDAC) was identified by our lab to be a T-cell mediated/Th1 sensitizer (Anderson et al ., 2016) using standard classifications schemes. However, clinical evidence suggests this LMW chemical can induce multiple types of hypersensitivity reactions (Geier et al ., 2013; Houtappel et al ., 2008; Vandenplas et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This laboratory has published data on numerous chemicals, generally classified as T H 2-mediated or IgE-mediated chemical sensitizers, including o -phthalaldehyde (OPA), glutaraldehyde, and toluene diisocyanate (TDI), that have induced elevations in IgE (local and total) at 10 days following four days of chemical treatment (Azadi et al 2004; Anderson et al 2010, 2016). In the present study, antibody levels were also examined following 14 days of continuous chemical application.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of DDAC showed similar trends for sensitization potential, IgE and immunophenotyping (surface markers and activation status) as DDAB; however, only the four-day exposure period was examined in the study and higher concentrations of DDAC (0.25–1%) were used compared to DDAB (Anderson et al 2016). These findings suggest that the hypersensitivity responses induced by DDAB might have different mechanisms and mediators based on exposure duration; while not analyzed in this study, it is possible that DDAC and other QAC may have similar exposure/duration mediated divergent mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation